PRASASTI HULUDAYEUH - Djafar, Hasan (Berkala Arkeologi, 1994)
The relics of the inscriptions in West Java were found scattered in several places, but until now the number is still small when compared to findings in the areas of Central Java or East Java. The inscription which is the object of this research is a stone inscription which is now located in the middle of a rice field in Huludayeuh block, Cikalahang Village, Kec. Source, Kab. Cirebon, West Java. Based on the name of the place where it was found, we call this inscription the Huludayeuh inscription. This inscription was issued as a sign of warning for the good efforts made by Sri Baduga Maharaja. Considering that the Huludayeuh inscription is related to the effort to commemorate the merits of Sri Baduga Maharaja, it is possible that this inscription was not issued by Sri Baduga Maharaja himself, but by his successor king, King Surawisesa (1521-1535).